Bibliotherapy Utilizing Electronic Publications to Increase The Self-Confidence of Teenagers Victims of Bullying - Nasution, Salsabila; Firman; Rezki hariko (Mimbar Ilmu, 2023)
Violence committed by teenagers is a complex and varied phenomenon; one form of violence often committed by teenagers is bullying. If bullying continues to occur, it will result in a decrease in trust and all aspects of the personal social life of the victim. This research aims to analyze the effectiveness of bibliotherapy using electronic publications in increasing the self-confidence of adolescent victims of bullying. This type of research is quantitative research with an experimental research type. The population in this study comprised vocational school students who were victims of bullying at school, totaling 67 students. The technique used to determine the sample is cluster random sampling. The number of samples in this study was 14 students. The methods used to collect data are observation and questionnaires. The instrument used to collect data was a questionnaire sheet. The data analysis technique in this research uses quantitative statistical analysis. Hypothesis testing uses Wilcoxon Signed Ranks Test data analysis. The research results are as follows: First, bibliotherapy using electronic publications effectively increases the self-confidence of teenagers who are victims of bullying in the experimental group. Second, bibliotherapy without electronic publications is effective in increasing the self-confidence of teenagers who are victims of bullying in the control group. Third, bibliotherapy using electronic publications is more effective in increasing the self-confidence of teenagers who are victims of bullying than bibliotherapy without using electronic publications. The implication of this research is that the application of Bibliotherapy by utilizing Electronic Publications can increase the self-confidence of adolescent victims of bullying.